Pola Naratif Film Dirty Vote II O3 terhadap Retensi Penonton Pada Platform Youtube - Rayhandy Jamal Pasha; Wahyu Nova Risky (CV. ITTC INDONESIA, 2026)
This study is motivated by the phenomenon of the documentary film Dirty Vote II O3, which has a four-hour duration yet remains capable of maintaining audience retention on YouTube amid the growing tendency of digital audiences to prefer short-form video content. This research aims to analyze the narrative patterns used in the film to sustain active audience retention. The study employed Robert K. Yin’s case study method with a pattern matching technique to compare the film’s narrative structure with YouTube’s Most Replayed audience retention graph. The research data were obtained through audiovisual documentation of the film, narrative transcripts, YouTube audience retention graphs, and literature studies relevant to Sheila Curran Bernard’s Documentary Storytelling theory. The findings reveal that audience retention is influenced by three primary narrative elements: train of thought, sequence of evidence, and narrative tension. The highest retention occurs when narrative conflicts are immediately reinforced by authentic evidence such as video footage, audio recordings, and visual documentation, while retention declines during overly conceptual segments lacking strong visual support. In addition, the division of the film into three main chapters proved effective in maintaining narrative pacing and audience engagement throughout the film’s duration. This study concludes that a systematically constructed narrative structure plays a significant role in sustaining digital audience retention in long-form political documentaries.